G115(P) Genetic and epigenetic variations and gene methylation in infants exposed to methadone in-utero. (27th April 2015) - Gillis, C; McLaughlin, P; Osselton, D; Hickish, T; Mactier, H
Abstract : Aims: Maintenance methadone for the treatment of opioid addiction in pregnancy is commonly associated with neonatal abstinence syndrome (NAS). NAS cannot be predicted in individual babies; differences may be explained at least in part by genetic variations. Gene function is also influenced by DNA methylation. We investigated whether single nucleotide polymorphisms (SNPs) in genes involved in methadone metabolism are associated with NAS, as well as methylation of these genes in opioid-dependent mothers and their babies and in controls. Methods: 21 methadone-prescribed opioid-dependent mother/infant pairs and 32 control mother/infant pairs. All babies were >36 weeks' gestation. Controls were selected as either non-smoking, DEPCAT 1–3 (affluent, n = 15) or smoking, DEPCAT 4–7 (deprived, n = 17). Buccal swabs were obtained for DNA analysis from mother/infant pairs within 5 days of birth. NAS was defined as symptoms severe enough to require pharmacological treatment. Results: Multiple different SNPs were analysed for 5 opioid-related genes. Methadone-exposed infants who required treatment for NAS were more likely to carry the wild type (normal) homozygous genotype at CYP2B6 516GT and 785AG compared to infants who did not require treatment. Infants exposed to methadone in-utero had significantly increased methylation of OPRM1 (receptor), ABCB1 (transporter) and CYP2D6 (metabolising) genes compared to controls (p < 0.005). Opioid-dependent mothers had increased methylation in only ABCB1 and CYP2D6 genes compared to controls. Conclusion: Infants with the homozygous CYP2B6 genotype are more likely to require treatment for NAS, consistent with the homozygous normal genotype being associated with faster metabolism of methadone. We have also shown that opioid dependency in pregnancy is associated with significant increases in methylation of at least three opioid genes in the newborn. Awareness of infant genotype may predict the severity of NAS and has potential to influence management of the neonate.